A tale of two beasts (Kane Miller, 2015)
There are two sides to every story. In part one, a little girl finds a strange beast in the woods and takes it home as a pet. She feeds it, shows it off to her friends and gives it a hat. But that night it escapes. Then, in part two, the beast tells the story of being kidnapped by the girl, who forcefed it squirrel food, scared it with a group of beasts and wrapped it in wool. Can the two beasts resolve their differences? An eye-opening story that makes you look at things from a different perspective.
Part one. The strange beast , Part two. The terrible beast.

Be Gentle!: a (Canclewick Press, 1997)
When Bartholomew gets a little black kitten, he must learn to take care of him and be gentle with him.

Lost cat (Houghton Mifflin Books for Children, 2013)
Slipper the cat is mistakenly left behind in the commotion when the lady she has always lived with moves in with her daughter's family, so Slipper sets out to find someone new to adopt.